TO THE 70TH ANNIVERSARY OF THE CHICAGO CONVENTION ON INTERNATIONAL CIVIL AVIATION - A. V. Neradyiko (Научный вестник МГТУ ГА)
The article is devoted to the prerequisite for the development and adoption of the Chicago Convention on International Civil Aviation of 1944. There are given the appreciation of the contents of the convention, it is shown its place and importance in the field of international air law. There is shown the current importance of the Chicago Convention for the development of international civil aviation.